2008
DOI: 10.1073/pnas.0712018105
|View full text |Cite
|
Sign up to set email alerts
|

X-inactivation in female human embryonic stem cells is in a nonrandom pattern and prone to epigenetic alterations

Abstract: X chromosome inactivation (XCI) is an essential mechanism for dosage compensation of X-linked genes in female cells. We report that subcultures from lines of female human embryonic stem cells (hESCs) exhibit variation (0 -100%) for XCI markers, including XIST RNA expression and enrichment of histone H3 lysine 27 trimethylation (H3K27me3) on the inactive X chromosome (Xi). Surprisingly, regardless of the presence or absence of XCI markers in different cultures, all female hESCs we examined (H7, H9, and HSF6 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
216
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(252 citation statements)
references
References 34 publications
30
216
2
4
Order By: Relevance
“…If this was the case, we would anticipate to see differences in diRNA activities on XIST associated lincRNAs TSIX [18,19] and FTX [20] between HEK and H9 cells. The two lincRNAs exhibited similar degrees of pxRNA activities between HEK and H9 ( Figure S4A-B), consistent with the observed XIST pxRNA activities and reported XCI in H9 cells [13]. However, TSIX and FTX exhibited much reduced diRNA activities in H9 as compared to HEK (Figure S4C-D), consistent with the minimal diRNA activity of XIST in H9.…”
Section: H9 Es Cells May Represent An Incomplete State Of X Chromosomsupporting
confidence: 85%
“…If this was the case, we would anticipate to see differences in diRNA activities on XIST associated lincRNAs TSIX [18,19] and FTX [20] between HEK and H9 cells. The two lincRNAs exhibited similar degrees of pxRNA activities between HEK and H9 ( Figure S4A-B), consistent with the observed XIST pxRNA activities and reported XCI in H9 cells [13]. However, TSIX and FTX exhibited much reduced diRNA activities in H9 as compared to HEK (Figure S4C-D), consistent with the minimal diRNA activity of XIST in H9.…”
Section: H9 Es Cells May Represent An Incomplete State Of X Chromosomsupporting
confidence: 85%
“…Xi erosion in hiPSCs and hESCs is believed to be closely associated with the loss of XIST and may broadly affect the characteristics of these cells [16,27]. These epigenetic modifications not only affect X-linked genes but also impact genome-wide gene expression, resulting in the upregulation of oncogenes and the downregulation of several tumor suppressors, thereby broadly affecting the characteristics of these cells [15][16][17][27][28][29][30]. Previous studies have suggested that female hiPSCs that have undergone XCI erosion should not be used clinically [16].…”
Section: Discussionmentioning
confidence: 99%
“…The ground-state mouse female ES cells or iPSCs have two active X chromosomes, whereas human female ES cells show signs of X chromosome inactivation detected by XIST expression or punctuate immunostaining pattern for H3K27me3 (31). qRT-PCR detected little XIST in our female iPSCs compared with the parental female dermal fibroblast cells (Fig.…”
Section: F Combination Readily Produces Human Ipscs That Resemble Mousementioning
confidence: 99%